2011
DOI: 10.1097/brs.0b013e3181e6ce16
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Effects of Spine Surgery Rods Composed of Different Metals and Alloys

Abstract: The shape of the hand contoured CPTi rods was the least stable of the rods across all applied temperature conditions. The SS and Ti-6Al-4V rods were more stable than CPTi rods. Autoclaving before handcontouring tended to increase rods' shape loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Unfortunately we did not have the opportunity to study the influence of all of these factors on springback in this study. However, previous publications have demonstrated that autoclaving significantly modifies thermo‐mechanical effects in medical rods manufactured from different metals and alloys 20, 21. Autoclaving is a routine procedure used in surgical practice for medical rods sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately we did not have the opportunity to study the influence of all of these factors on springback in this study. However, previous publications have demonstrated that autoclaving significantly modifies thermo‐mechanical effects in medical rods manufactured from different metals and alloys 20, 21. Autoclaving is a routine procedure used in surgical practice for medical rods sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of shape loss was suggested by Noshchenko et al 7 to be detrimental to the spine fusion constructs, even though it was relatively small. 7 This is of concern because previous literature has also suggested that CPTi rods are prone to shape loss after autoclaving and manual bending. 6 This was reproduced in our study because all CPTi rods (in addition to all CoCr rods) demonstrated statistically significant loss of shape over time.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior studies, the rate of shape loss was highest during the first 2 days of the study and then decreased to a rate approaching zero by 8 weeks. 6,7 This early shape loss is likely a result of elastic recoil. That is, the amount of deformation created was not enough to surpass the yield point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ti-6Al-4V is stronger and stiffer than Commercially Pure Titanium, readily available, and easily to machine. After contouring, such as in the case of spinal rods, Ti-6Al-4V also holds its shape better over temperature changes than commercially pure titanium (Noshchenko et al 2011). Titanium-molybdenum is more difficult and expensive to obtain, and requires advanced expertise in machining, due to its nature of clogging cutting tools.…”
Section: Metallic Implantsmentioning
confidence: 99%